GAP ARTHROPLASTY PADA BONY ANKYLOSIS SENDI TMJ (LAPORAN KASUS) - Alice Wenas; Alwin Kasim (Faculty of Dentistry, Universitas Indonesia, 2015)
A case of unilateral bony ankylosis of the temporomandibular joint (TMJ) in a thirteen year old girl was reported. Maximum opening was minimal (4 mm) with hypoplastic mandible and also facial and dental asymmetry. There was no palpable movement over the left TMJ and only slight rotation on the right side. It may be caused by trauma, but the parents didn't notice. She had a problem with sleep apneu and sometimes felt sleepy during school time. She was refered to Oral Surgery Department Hasan Sadikin Hospital in Bandung from a private dental practitioner in Jakarta. Treatment for this patient is divided into three operations. The first operation was gap arthroplasty, second operation is osteodistraction and followed by orthognatic surgery. This paper discusses only gap arthroplasty with temporoparietalis muscle interposition. Twenty days after surgery, maximum opening was 26 mm.